XND1-centered network regulates salt tolerance by integrating root xylem plasticity and Na + unloading in Arabidopsis - Bingli Ding; Yafei Shi; Runling Zhang; Mengyu Liang; Xiaohu Sun; Yupu Huang; Christophe Maurel; Ning Tang (Proceedings of the National Academy of Sciences, 2025)
Soil salinization has emerged as a significant challenge for crop production worldwide. Xylem adjustments through plastic development and sodium unloading from root xylem, as mediated by sodium transporter HKT1, both play crucial roles in controlling sodium transport and salt tolerance in plants. Here, we report that XYLEM NAC DOMAIN 1 (XND1) of Arabidopsis contributes to the coordination of these two processes during salt stress responses. XND1 is predominantly accumulated in roots under salt exposure and confers plant salt tolerance, as demonstrated by analysis of overexpression and loss-of-function mutant lines. XND1 mediates discontinuous root protoxylem differentiation under salt stress, potentially limiting sodium transport. In addition, XND1 directly targets and activates the expression of HKT1 , thereby facilitating the removal of sodium from root xylem. We also show that MYBS2, a MYB transcription factor, interacts with XND1 to antagonistically regulate HKT1 , whereas VND-INTERACTING 2 (VNI2), a NAC transcription factor, activates XND1 in response to salt stress. Characterization of the XND1 ortholog of rice suggests a conserved regulatory role under salt stress. Collectively, our findings unveil an XND1-centered regulatory network that modulates salt stress response, through the integration of root xylem developmental plasticity and sodium unloading.